Making Camp - Lola Sheppard (Oz, 2016)
A foundational myth of North America is our collective relationship to our expansive, often rugged, and remote national landscapes. From Thoreau’s cabin in the woods, to nineteenth century cottages offering urbanites respite from the city in the summer seasons, the notion of retreat and the restorative role of immersive landscape experiences has formed part of the North American conscience.